Regeneration of Spent Nickel Catalyst via Hydrometallurgical Method - Amelia, Fransisca Poppy; Sari, Erica Puspita; Norman, Hafiz; Salsabil, Muhammad Alhadilansa; Yudha, Cornelius Satria (Equilibrium Journal of Chemical Engineering, 2023)
Abstract. Nickel Catalyst is one of the common catalysts found in chemical industries. However, this catalyst has a limited lifetime indicated by having performance or activity drop so it is potentially become dangerous waste if the handling is not proper. The spent nickel catalyst needs to be processed to recover and avoid pollution towards the environment. The Hydrometallurgy method is a proper method to process nickel catalyst waste. The purpose of this research is to investigate the characteristic of a regenerated nickel catalyst when it is treated with HCl and H2SO4 as the lixiviant. In this research, the spent nickel catalyst was treated with HCl and H2SO4 in the presence of 2% H2O2 reductant under room conditions and mixing rate at 200 rpm for 30 minutes of reaction. The leaching filtrate was precipitated using NaOH solution while the formed precipitate was heated at 800 °C for 3 hours. The regenerated catalyst was characterized using FTIR and SEM-EDX. The SEM images showed regenerated catalyst prepared using the HCl solution has a different morphology compared to the one using the H2SO4 solution. Based on FTIR analysis, both samples exhibit Ni-O and C-O groups. Based on elemental analysis, the highest nickel concentration was obtained by using HCl with a Ni content of 25.98%w/w, compare to sulfuric acid (H2SO4) with a Ni content of 10.94%w/w. The Ni content can be improved by the addition of a washing step after the sintering process.Keywords:Hydrometallurgy Nickel Catalyst, Waste, Leaching, Sintering